Turbulent forced convection of nanofluid in a heated tube: A Computational Fluid Dynamics (CFD) study / Iman Behroyan - Iman , Behroyan (2013)
In this study, turbulent forced convection of Cu-water nanofluid inside a horizontal pipe with a constant wall heat flux is investigated numerically. Two types of approaches are used; one is based on a single-phase model and the other is Eulerian-Eulerian two-phase models. The mass, momentum and energy equations are solved using control volume method (FVM) and commercial codes of ANSYS-Fluent. The simulation results of both models are compared to the existing experimental results. The simulation results for Cu-water nanofluid show that the homogeneous model, i.e., the single model is not able to predict the Nusselt number accurately for all particle fractions and Reynolds numbers. The two-phase model in Fluent can estimate the Nusselt number of nanofluid accurately, only with the use of reasonable effective particles thermal conductivities. The best effective particles conductivities are calculated based on trial and error method for some typical Reynolds numbers and particles volume fraction. Finally several correlations are developed to predict particles conductivity as a function of Reynolds number at each particle concentration. The general trend of correlations shows a linear increasing trend of the particles conductivity versus the Reynolds number.